Adolescent prosocial and antisocial behaviours: simultaneous effects of self-control, attitudes of parents and teachers - Ketut, Gading; Hassan, Siti Aishah; Omar, Rosmaria; Hanafi, Norshafizah (Universiti Putra Malaysia, 2024)
This study investigates the complex relationships between parental attitudes, teacher attitudes, and self-control and their associations with prosocial and antisocial behaviour among adolescents in Bali, Indonesia. The research utilises a correlational research design with structural equation modelling (SEM) analysis to examine the relationships among variables comprehensively. A sample of 260 high school students aged 14 to 16 in Bali, Indonesia, was selected using a multi-stage cluster random sampling technique with 104 male and 156 female. The standard deviation of age is 0.49. Data were collected using adapted instruments to measure prosocial behaviour, antisocial behaviour, parents’ attitudes, teachers’ attitudes, and self-control. The study found positive correlations between parental attitudes, teacher attitudes, self-control, and prosocial behaviour and negative correlations with antisocial behaviour. The SEM analysis produced a predictive model for adolescent prosocial and antisocial behaviour, demonstrating strong compatibility with the model. The results indicated that parents’ attitudes, teachers’ attitudes, and self-control contributed significantly to prosocial behaviour among adolescents. However, while teachers’ attitudes and self-control were significantly related to antisocial behaviour, no significant relationship was found between parents’ attitudes and antisocial behaviour. The findings provide valuable insights into the role of parent-child relationships and highlight the potential for fostering positive behavioural outcomes. The study’s contribution lies in its focus on multiple dimensions of relationships and its exploration of the impact of parental difficulties. Ultimately, this research deepens the understanding of prosocial and antisocial behaviour and its underlying mechanisms, shedding new light on the field of prosocial.